Joint Ownership Expenses According to The Mecelle - Ki̇sbet, Mustafa (Bursa Uludağ Üniversitesi, 2022)
The rules regarding the sharing of the repair and maintenance costs of the joint ownership, which are scattered in various parts of the fiqh books, are itemized under a single title in the Mecelle. It is essential that the partners participate in such expenses according to their shares. However, it is natural that the partners cannot always agree on issues such as the necessity of repairs, how to do it, and the sharing of costs. Based on examples such as common building and wall in the Mecelle, the way to be followed in such disputes is shown. Accordingly, repairs must be made with the permission of the other partner or with a court decision if the other partner does not accept the repair offer. Otherwise, the repairing partner cannot recourse to the other partner for cost sharing. If the division of the common property is possible, the court cannot force the parties to repair and the property is divided according to the shares. If the division of the property is not possible, the partner who makes the repairs with a court decision demands from the other partner the amount that falls on his share from the expense. If the partner whose repair proposal is not accepted proceeds without a court order, the costs are shared by the amount of increase in the value of the building divided by the shares. In the examples of lower-upper neighbors, there are provisions that the floor owners have the right to rebuild the building as before in case the building is demolished, that the owner of the upper floor can also have the lower floor built by obtaining permission from the court, and that the owner of the upper floor can prevent the owner of the lower floor from disposing of property until he receives the cost. If the neighbors have bearing walls between their buildings, they must participate in its repair. If the wall is to protect privacy and if it is torn down, rebuilding is not necessary and a barrier must be built in its place. The judge in the common court represents the absentee. The guardians and trustees of the persons who do not have the capability of performance have to participate in the necessary repairs.

Fıkıh kitaplarının çeşitli bölümlerinde dağınık olarak bulunan ortak mülkiyetin tamir ve bakım masraflarının paylaşımı ile ilgili kurallar, Mecelle’de tek başlık altında maddeleştirilmiştir. Bu tür masraflara ortakların hisselerine göre katılmaları esastır. Ancak ortakların tamir işlemlerinin gerekliliği, nasıl yapılacağı ve masrafların paylaşımı gibi konularda her zaman anlaşamayacakları tabiidir. Mecelle’de ortak bina ve duvar gibi örneklerden hareketle böyle anlaşmazlıklarda takip edilecek yol gösterilmiştir. Buna göre tamir işlemlerinin diğer ortaktan izin alınarak veya diğer ortağın tamir teklifini kabul etmemesi üzerine mahkeme kararı ile yapılması gerekir. Aksi hâlde tamir yapan ortak, masraf paylaşımı için diğer ortağa rücu edemez. Ortak mülkün taksimi mümkün ise mahkeme tarafları tamire zorlayamaz ve mülk hisselere göre taksim edilir. Eğer mülkün taksimi mümkün değilse mahkeme kararı ile tamir işlemlerini yapan ortak, diğer ortaktan masraftan hissesine düşen miktarı talep eder. Tamir teklifi kabul edilmeyen ortak, mahkeme kararı olmadan işlem yaparsa, masraflar binanın değerindeki artış miktarının hisselere bölünmesi ile paylaşılır. Alt-üst komşuluk örneklerinde ise binanın yıkılması hâlinde kat sahiplerinin binayı eskisi gibi yapma hakları, üst kat sahibinin mahkemeden izin alarak alt katı da yaptırabileceği, üst kat sahibinin masrafını alana kadar alt kat sahibini tasarruf etmekten engelleyebileceği hükümleri yer alır. Komşuların, binaları arasındaki duvar, taşıyıcı ise tamirine katılmaları gereklidir. Eğer duvar mahremiyeti koruyorsa yıkılması durumunda yeniden inşası gerekli olmayıp yerine bir engel inşa edilmelidir. Gaip ortak, mahkemede hâkim tarafından temsil edilir. Eda ehliyetine sahip olmayan kişilerin vasîleri ve vakıf mütevellileri, gerekli olan tamir işlemlerine katılmak zorundadır.
Keywords: İslâm Hukuku; Mecelle; Ortaklık; Müşterek Mülkiyet; Komşuluk; Masraf; Tamir; Bakım.; Islamic Law; Mecelle (Medjelle); Partnership; Joint Ownership; Neighborhood; Cost; Repair; Maintenance Expense.; Islamic Law; Mecelle (Medjelle); Partnership; Joint Ownership; Neighborhood; Cost; Repair; Maintenance Expense.